'Shama will not dance': University of Khartoum politics, 1964–69. (16th January 2019) - Glade, Rebecca
Abstract: In 1968, the Democratic Front organized a folkloric dance recital at the University of Khartoum as a prelude to the upcoming student union elections, a recital that was opposed by the Islamic Movement. This dispute culminated in a riot in which a student was killed, an event referred to as the ' Ajako incident', which is discussed as the first recorded instance of inter-student violence at the university. Drawing on newspaper accounts from the time, secondary sources and first-hand interviews with participants, this article explores the clashing political and moral ideologies at stake within the University of Khartoum, and their links and affective power in relation to Khartoum politics more widely. In the process, it argues that the student political sphere did not simply function as a mirror to the wider political environment, but rather as a mobilizing ground for ideologically based parties, allowing more radical youth groups to influence national dialogues and put pressure on national political actors. Résumé: En 1968, le Front démocratique organisa un récital de danse folklorique à l'université de Khartoum en prélude à des élections de syndicats étudiants, récital auquel s'opposait le Mouvement islamique. Ce conflit provoqua des émeutes qui firent un mort parmi les étudiants. Premier cas recensé de violence entre étudiants à l'université, cet évènement appelé « l'incident d' Ajako » est le sujet de cet article. S'appuyant sur les faits rapportés par la presse de l'époque, sur des sources secondaires et sur des entretiens avec des protagonistes, cet article explore les idéologies politiques et morales qui s'affrontaient à l'université de Khartoum, ainsi que leurs liens et leur pouvoir affectif au regard de la politique de Khartoum plus largement. Ce faisant, l'article soutient que la sphère politique étudiante ne fonctionnait pas simplement comme le miroir de l'environnement politique plus large, mais plutôt comme un terreau mobilisateur pour les partis à base idéologique, qui permettait à des groupes de jeunes plus radicaux d'influencer le dialogue national et de faire pression sur les acteurs politiques nationaux.